PENGARUH PENGUNGKAPAN ENVIRONMENTAL SOCIAL AND GOVERNANCE (ESG) TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR TAHUN 2019-2023) - Salmah, Sayyidatus; Afriyenti, Mayar (Universitas Pasundan, 2025)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure on firm value among manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The independent variables consist of environmental, social, and governance disclosures, while the dependent variable is firm value, measured by the Tobin’s Q ratio. The study adopts a quantitative approach with a causal research design and uses purposive sampling, resulting in 16 companies as the research sample over five years of observation (80 data points). Data analysis was conducted using panel data regression with EViews software. The results reveal that environmental disclosure has a significant positive effect on firm value, indicating that broader environmental transparency enhances investor confidence. Social disclosure also shows a positive and significant influence, implying that strong social responsibility improves corporate image and stakeholder trust. Meanwhile, governance disclosure exhibits a positive but insignificant effect on firm value. Overall, the three ESG components jointly have a significant impact on firm value. These findings highlight the importance of integrating sustainability principles through ESG disclosure as a strategic tool to enhance the value of manufacturing companies in Indonesia.